UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS MAHASISWA MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH PADA PROGRAM STUDI KEWIRAUSAHAAN UNIVERSITAS AUFA ROYHAN - yulia pratiwi siregar (JURNAL MathEdu (Mathematic Education Journal), 2022)
This study aims to determine the students' mathematical understanding ability, early ability students with early ability high, medium, and moderate initial abilities in the 3rd semester entrepreneurship of program study students. The improvement of students' mathematical understanding skills is carried out using a problem-based learning model. This research was carried out by applying the Qualitative Research method. Informants in this study were the Head of the Study Program and students who were taken using the Total Sampling technique. Data collection techniques used field notes, tests, interviews, and documentation. Data analysis was performed using data reduction. The results showed (1) students who had high early mathematical abilities had very good mathematical understanding abilities, (2) students who had moderate early mathematical abilities had good mathematical understanding abilities, and (3) students who had low mathematical abilities had low mathematical abilities sufficient mathematical understanding.